Effect of combination antiretroviral therapy on human immunodeficiency virus 1 specific antibody responses in subtype-C infected children. (11th December 2020) - Kumar, Sanjeev; Batra, Himanshu; Singh, Swarandeep; Chawla, Himanshi; Singh, Ravinder; Katpara, Sanket; Hussain, Abdul Wahid; Das, Bimal Kumar; Lodha, Rakesh; Kabra, Sushil Kumar; Luthra, Kalpana
Abstract : Protective antibody responses to human immunodeficiency virus (HIV)-1 infection evolve only in a fraction of infected individuals by developing broadly neutralizing antibodies (bnAbs) and/or effector functions such as antibody-dependent cellular cytotoxicity (ADCC). HIV-1 chronically infected adults and children on combination antiretroviral therapy (cART) showed a reduction in ADCC activity and improvement in HIV-1 specific neutralizing antibody (nAb) responses. Early initiation of cART in infected adults is found to be beneficial in reducing the viral load and delaying disease progression. Herein, we longitudinally evaluated the effect of cART on HIV-1 specific plasma ADCC and nAb responses in a cohort of 20 perinatally HIV-1 subtype-C infected infants and children ≤2 years of age, pre-cART and up to 1 year post-cART initiation. Significant reductions in HIV-1 specific plasma ADCC responses to subtype-C and subtype-B viruses and improvement in HIV-1 neutralization were observed in HIV-1 infected children 1 year post-cART initiation. A positive correlation between reduction in viral load and the loss of ADCC response was observed. This study provides information aiding the understanding of the effects of early initiation of cART on antibody effector functions and viral neutralization in HIV-1 infected children, which needs to be further evaluated in large cohorts of HIV-1 infected children on cART to plan future intervention strategies.